Genetic restriction in two conserved regions of Plasmodium falciparum EBA 175. (1999)
The 175 kDa erythrocyte binding antigen (EBA-175), first reported by Camus and David [I], is a Plasmodium falciparum specific protein involved in the primary merozoite-erythrocyte interaction. It shares the general primary structure pattern and general intron—cxon organization characterizing other proteins involved in the target cell recognition by malarial parasites such as the Duffy receptor of P. vivax and P. knowlesi, the reticulocyte binding protein of P. vivax and the apical merozoite antigen 1 of P. falciparum [2]. This fact raised the hypotheses for their consideration as a protein family.